S8 Hyperpolarised 3He MRI is superior to lung clearance index in detection of ventilation abnormalities in young children with mild CF. (14th November 2013) - Marshall, H; Horsley, A; Smith, L; Hughes, D; Horn, F; Armstrong, L; Parra-Robles, J; Cunningham, S; Aldag, I; Taylor, C; Wild, Jm
Abstract : Introduction: Hyperpolarised 3 He MRI provides high resolution images of lung ventilation and is more sensitive than spirometry to early changes in lung ventilation in cystic fibrosis (CF). Lung clearance index (LCI) is a global measure of ventilation heterogeneity which is also sensitive to early changes in the lungs in CF before spirometry. The aim of this study was to investigate the capability of hyperpolarised 3 He MRI and LCI to detect ventilation changes in children with mild CF. Methods: 4 CF patients (FEV1 78 110% predicted) and 4 healthy volunteers have been assessed so far. 3 He ventilation images were acquired at breath-hold following inhalation of hyperpolarised 3 He, with 2.7x2.7x10mm resolution and full lung coverage using a 1.5T MRI system. The percentage of lung ventilated (VV%) was calculated as 3 He ventilated volume divided by total lung volume segmented from 1 H MR images. LCI was measured using 0.2% SF6 and a modified Innocor gas analyser. LCI was performed sitting and repeated supine to mimic the position adopted for MRI scanning. Spirometry and plethysmography were also performed. Gas trapping was calculated as% difference in plethysmographic versus washout FRC. Results: Healthy volunteers had a mean (standard deviation) age of 8.8(1.5) years, FEV1 % predicted = 97(10) and gas trapping = 4.4(9.1)%. LCI sitting was 6.9, 7.3, 6.6 and 6.9, LCI supine was 7.3, 7.5, 6.8 and 6.4. Healthy volunteers had homogeneous ventilation in 3 He ventilation images e.g. Fig1(a), and VV% = 94.5(2.8). CF patients had an age of 11.8(2.9) years, FEV1 % predicted = 95(13), and gas trapping = 8.7(11.0). LCI sitting was 7.7, 6.6, 6.6 and 9.1, LCI supine was 7.8, 7.3, 7.1 and 11.8. Ventilation abnormalities were observed using 3 He MRI in all four CF patients scanned (Fig 1 (b-e), with order corresponding to the LCI values given), and VV% = 89.2(2.6). 2 of the 4 CF patients had normal sitting and supine LCI and 2 of 3 had no evidence of gas trapping, but 3 He MRI showed clear focal ventilation defects in all patients (b-d). Conclusions: High quality 3 He MRI images can be produced in young children. Preliminary results suggest that hyperpolarised 3 He ventilation MRI may be more sensitive to early ventilation changes in CF than LCI or conventional lung function tests. Acknowledgements: CF Trust funding